Psychological Features of Test-taking Anxiety in Adolescent Students and Practices for its Reduction - Petar Neshev (Педагогически форум, 2025)
The article examines the psychological features of test-taking anxiety in adolescent students. The impact of different coping strategies is presented. Practices that can help students manage anxiety are examined. Personal characteristics of the student that predispose to higher levels of anxiety are described. Different scientific approaches to the problem under study are compared. The applicability of the approaches for developing skills for dealing with anxiety in a learning environment is indicated. The practical benefits of using various techniques for controlling and reassessing the exam situation are revealed. Suggested are different active coping strategies and parental support leading to reduction of disturbing thoughts and to lead to improvement in school performance.